Perilaku Pencarian Informasi Petani dalam Budidaya Gambir di Jorong Tanjuang Bungo Nagari Koto Lamo Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Azzahra, Puti Zahwa; Nabila, Jeihan (Lembaga Yasin AlSys, 2024)
This study aims to describe the information seeking behavior of farmers in gambier cultivation in Jorong Tanjuang Bungo. The method used is a qualitative method using interviews to collect data. The interviews involved ten farmers in Jorong Tanjung Bungo. Data were collected through four stages, namely passive attention, passive search, active search, and continuous search. Results show that in the passive attention stage, farmers rely on TV and Radio if the signal is stable and social interaction. The passive search stage is characterized by receiving unexpected information through communication. In the active search stage, farmers use external resources such as actively engaging in various communities. The continuous search stage shows farmers' efforts to expand their knowledge and improve farming practices. Therefore, there are obstacles faced by farmers in gambier cultivation in the process of searching for information which includes the lack of media used to search for information so that the information searched shows little information because of one source only.